2018
DOI: 10.1177/1741143218792914
|View full text |Cite
|
Sign up to set email alerts
|

Ethics education in leadership development: Adopting multiple ethical paradigms

Abstract: Attitude development and identity formation in educational leadership are the goals of non-traditional, and in the 21st century also of neo-traditional, development initiatives. Ethics education emerges as one of the linchpins in neo-traditional and non-traditional development initiatives. Yet, despite considerable interest in ethics education in educational leadership development, ethics education has not been examined systematically, and empirical research on its effects is scarce. The present paper aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 36 publications
1
33
0
1
Order By: Relevance
“…In relation to the concept of sustainable management (Figure 1, concept 8), this is defined as a decalogue of human, ethical, and environmental values, with the purpose of providing societies with an instrument for the sustainable development of companies, institutions, and communities, thus ensuring competitiveness and strengthening the global economic and social fabric [60][61][62].…”
Section: Sustainability 2020 12 X For Peer Review 4 Of 24mentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the concept of sustainable management (Figure 1, concept 8), this is defined as a decalogue of human, ethical, and environmental values, with the purpose of providing societies with an instrument for the sustainable development of companies, institutions, and communities, thus ensuring competitiveness and strengthening the global economic and social fabric [60][61][62].…”
Section: Sustainability 2020 12 X For Peer Review 4 Of 24mentioning
confidence: 99%
“…In addition, the term "university involvement" is attached, so that research places value on institutions that adopt methods of participation, and this capacity is related to those that have a high quality strategy, rather than a minimization one, of costs. This term also connects with the "organizational control in university management" [62,141]. In line with the new keywords that are associated with this area of research, it is necessary to point out "blockchain university" [142].…”
Section: Keyword Analysismentioning
confidence: 99%
“…Branson said, "It is through the bringing of naturally existing unconscious inner phenomena into their consciousness that initiates educational leaders' progress toward becoming ethical leaders" (p. 199). Other researchers agree with Branson that a school leader's inner experiences and personal values are significant influences on their problem-solving and ethical leadership behaviors and are worthy of intensive selfreflection and identification (Bebeau, 2008;Berkovich & Eyal, 2018;Boske et al, 2017;Branson & Gross, 2014;Daniels, 2003;Drago-Severson et al, 2018;Langlois & LaPointe, 2010;Mullen, 2017;Pauken, 2012;Rintoul & Goulais, 2010;Tuana, 2014).…”
Section: Leaders' Internal Experiencesmentioning
confidence: 99%
“…Lindle (2004) concurred, stating that K-12 schools are not "safe spaces" for educators to practice critical thinking, or thinking that may contradict the culture and norms of the school. Cummings et al (2007) suggested that perhaps the field of education actually attracts or "self-selects" students who are less inclined to be critical thinkers, preferring to apply preformed moral schemas to ethical decision making (Berkovich & Eyal, 2018). Cummings et al further offered that the content and expectations of education preparation curricula are too technical and task oriented to provide a strong context for moral development among education students.…”
Section: Concerning Nature Of the Findingsmentioning
confidence: 99%
“…Another type of challenging ethical dilemma occurs when the educational leader has an educational agenda, and the student and his/her family do not concur on this agenda (Grootenboer and Hardy, 2017). Moreover, ethical dilemmas also often appear when interested parties hold different ideas about what is ‘good’, leading to disagreements about whose viewpoint should be accepted (Berkovich and Eyal, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%